Kedudukan Permenkumham Nomor 17 Tahun 2018 dalam Menjamin Kepastian Berusaha Persekutuan Komanditer - Faisal, Mochammad Aznawi; Sihabudin, Sihabudin; Hadiyantina, Shinta (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2021)
This study aimed to analyze changes in the provisions for registering limited partnership after enacting the Minister of Law and Human Rights Regulation Number 17 of 2018 and the position of Minister of Law and Human Rights Regulation Number 17 of 2018 on the hierarchy of laws and regulations in Indonesia. The type of research used was normative juridical law with a conceptual, historical, and statutory approach. After the enactment of Minister of Law and Human Rights Number 17 of 2018, the authority to register limited partnerships, which was previously the authority of the Minister of Trade, was transferred to the Minister of Law and Human Rights. The position of Minister of Law and Human Rights Regulation Number 17 of 2018 is seen from the procedure for forming ministerial regulations that do not meet the requirements as implementing regulations and are contrary to the principle of business certainty.